Post a New Question

Math

posted by on .

Evaulate each expression:

(-1/8)^1/3

Would you make it 3 square root of -1/8? I don't know how to go from there.

(256/81)^1/4

Same thing, would it become 4 square root (256/81)?

  • Math - ,

    (-1/8)^1/3
    = (-1)^(1/3) / 8^(1/3)
    = -1/2

    check: (-1/2)(-1/2)(-1/2) = -1/8

    (256/81)^(1/4) ---- the fourth root
    = 4/3

    exponents in fraction form are roots
    1/3 is cube root
    1/4 is fourth root, etc

    if you have an exponent like 2/3,
    look at it as 2(1/3)

    so 8^(2/3)
    could be (8^2)^(1/3) = 64^(1/3) = 4
    or
    (8^(1/3) )^2= 2^2 = 4

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question